Healthy, Wealthy and Working: Retirement Decisions of Older New Zealanders - James Enright; Grant M Scobie (New Zealand Government, The Treasury, 2010)
Health status is an important element in the decision to continue working or retire among older workers. Given the demographic projections for the next four decades, there will be increasing opportunities for older workers to remain in the workforce. However, an individual's decision is likely to be influenced by both their health status and their accumulated wealth. This study analyses the influence of health and wealth on the decision to participate in the labour force amongst older New Zealanders, aged 55 to 70. It is based on the first wave of data collected in a longitudinal survey of Health, Work and Retirement conducted by researchers at Massey University. The study employs a range of measures of health including the results from the international Short Form (SF36), self-reported health status and the prevalence of chronic illness. Regardless of the measures tested, a significant reduction in labour force participation is associated with poorer health status. It is widely recognised that health status itself may partly be determined by labour market characteristics. Attempts to deal with this statistically were not successful. Perhaps surprisingly, wealth did not appear to be strongly related to the decision to retire. A marked fall in participation is associated with the receipt of New Zealand Superannuation at age 65, arguably masking the effect of privately held forms of retirement wealth. The paper reports associations between health, wealth and retirement which do not necessarily constitute evidence of causality.
Keywords: D19; D31; J22; J26; 330; Health; Wealth; Labour Supply; Retirement; New Zealand; Gesundheit; Soziale Lage; Erwerbstätigkeit; Ältere Arbeitskräfte; Flexible Altersgrenze; Neuseeland